Process development for recovery of dysprosium from permanent magnet scraps leach liquor by hydrometallurgical techniques†. (30th October 2015) - Yoon, H.-S.; Kim, C.-J.; W. Chung, K.; Kim, S.-D.; R. Kumar, J.
Abstract : The aim of the present study is to investigate the extraction, separation and recovery of the indivisible metals of dysprosium and neodymium from permanent magnets scrap (PMS) leach liquor solutions. Organo-phosphorous extractant namely 2-ethylhexyl phosphonic acid mono-2-ethylhexyl ester (PC 88A) was employed and optimised various experimental parameters to recover dysprosium. The present experimental development focused on Dy separation from Nd and recovery by suitable mineral acids. Fundamental studies of the effect of time, pH and extractant concentration on the metal separation were conducted followed by proposal of a mechanism for extraction. Process development included generation of McCabe–Thiele diagrams and counter current extraction (CCE) studies. Generation of loaded organic phase from the CCE process was followed by scrubbing studies and final recovery of Dy. Comparisons were made between two types of phase ratios as well as with already reported methods on title metal ions extraction and separation processing. For the metal content analysis in the aqueous samples, advanced analytical instrument such as inductively coupled plasma spectrometer (ICP-OES) was used to obtain sensitive and accurate data.